A human immune dysregulation syndrome characterized by severe hyperinflammation with a homozygous nonsense Roquin-1 mutation - S. J. Tavernier (Nature Portfolio, 2019)
Roquin-1 is a posttranscriptional regulator that controls the expression of many immune-related genes such as ICOS and TNFA. Here, the authors report a homozygous R688* loss of function mutation in Roquin-1 in a patient with syndromic uncontrolled hyperinflammation associated with immune cell activation and hypercytokinemia.